2021
DOI: 10.1002/qj.4017
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution climate change projection of northeast monsoon rainfall over peninsular India

Abstract: In this study, projected changes in mean northeast monsoon (NEM) rainfall and associated extreme rainfall and temperature events, over peninsular India (PI) and its six subdivisions, are quantified. High-resolution dynamically downscaled simulations of the Weather Research and Forecasting (WRF) regional climate model driven by the boundary conditions from the Community Climate System Model version 4 (CCSM4) model (WRF-CCSM4) are compared with statistically downscaled simulations of NASA Earth Exchange Global D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…In addition, 15% of farmers reported that flooded fields were a main reason that they delayed wheat sowing, as they were unable to prepare fields when there was standing water. This is of concern given that within-season rainfall distributions are changing due to climate change, with some models projecting increases in end of season monsoon rainfall (Loo et al 2015, Jayasankar et al 2021. This could be problematic for the establishment of wheat if higher rainfall at the time of rice harvest and wheat planting leads to increases in water logging in fields.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 15% of farmers reported that flooded fields were a main reason that they delayed wheat sowing, as they were unable to prepare fields when there was standing water. This is of concern given that within-season rainfall distributions are changing due to climate change, with some models projecting increases in end of season monsoon rainfall (Loo et al 2015, Jayasankar et al 2021. This could be problematic for the establishment of wheat if higher rainfall at the time of rice harvest and wheat planting leads to increases in water logging in fields.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, our future climate analysis also shows that, with a steep decline in the suitable range, the southern and parts of the Western Ghats might act as a climate refugia for the D. hololius under the RCP 8.5 for 2070. The climate change analysis from the past studies for the Peninsular Indian region shows that increase in drought (Rehana and Naidu, 2021) and extreme rainfall events clubbed with warmer winter months (Jayasankar et al, 2021). Insofar as amphibians are ectothermic animals with an amphibious life cycle, events like erratic rainfall, warmer winter months, and increased temperature will only increase the species' vulnerability (Cushman, 2006;Buckley and Jetz, 2007), which is overwhelmed by human-induced land-use changes, especially in this case.…”
Section: The Potential Distributionmentioning
confidence: 95%
“…The coastal Andhra plain has a large population, and the region receives enough rainfall during the monsoon and post-monsoon seasons to maintain it (Murthy , 2020). Due to unprecedented and erratic rainfall events and nonavailability of surface water, groundwater depletion, and salinity problems in coastal regions, they affect developmental activities and the living standards of the population (Jayasankar , 2021). Keeping this in mind, the current study was conducted in the West Godavari district of coastal Andhra Pradesh to examine the climate pattern utilizing water balance methodologies and historical data spanning the period 1901-2019.…”
Section: Introductionmentioning
confidence: 99%